Financial strain and smoking cessation among men and women within a self-guided quit attempt. (August 2015) - Reitzel, Lorraine R.; Langdon, Kirsten J.; Nguyen, Nga T.; Zvolensky, Michael J.
Abstract: Introduction: Financial strain, defined as an unfavorable asset-to-needs ratio, has been associated with reduced odds of smoking cessation in the context of a structured clinical study providing cessation assistance. This study reports on a secondary data analysis that assessed the association of financial strain and biochemically-verified smoking abstinence within a structured clinical study of smokers making a self-guided cessation attempt. Methods: Participants ( N = 58; 65.5% men) were enrolled in a study about anxiety sensitivity and smoking cessation whereby they were instructed to initiate a self-guided quit attempt. Relations between financial strain and biochemically-verified smoking abstinence on the quit day and at Days 3, 7, 14, 28, and 90 post-quit were assessed using generalized estimating equations controlling for age, sex, race, education, partner status, pre-quit cigarettes smoked per day, and time. Results: Associations between financial strain and abstinence in the whole sample were marginal (aOR = .94, 95% CI = .87–1.01, observations = 293; p = .07). However, sex was a significant moderator: greater financial strain was associated with lower odds of abstinence for men (aOR = .90, 95% CI = .80–1.00, observations = 201; p = .05), but not women (aOR = 1.05, 95% CI = .91–1.21, observations = 92; p = .48). Conclusions: Results indicated that financial strain was associated with lower odds of cessation among men undergoing a self-guided quit attempt in the context of a structured clinical study. These data suggest that financial strain may be an important socioeconomic determinant of smoking cessation and support its relevance for better understanding socioeconomic-based smoking-related health disparities. Future work may benefit by exploring sex-specific models of financial strain in the context of smoking cessation. Highlights: Financial strain and smoking abstinence were examined among self-guided quitters. Financial strain predicted lower odds of CO-confirmed abstinence among men only. Financial strain may play a unique role in socioeconomic-based smoking disparities. Studies should explore if sex-specific models aid in understanding these relations.